A review on the Malaysian laws relating to public playground with special reference to Shah Alam / Nur Ainnabila Rosdi … [et al.] - Rosdi, Nur Ainnabila; Mohd Azham, Siti amalia; Raja Alauddin, Raja Nur Zamira; Mohamad Hanapi, Nuurul Atila (2013)
This project paper describes the issue of children's safety in public playground with special reference to Shah Alam. It reviews on legislations and approaches in other jurisdiction and examines the role of the relevant authorities in the construction, maintenance and supervision of the children's playground. The risk of injury at the public playground in Malaysia is on a hike, but the responsible bodies in overcoming this situation have done little. Therefore, this paper aims to analyse the available laws governing the safety of playground in Malaysia namely the common law position, Local Government Act 1976, Consumer Protection Act 1999 and Parks (Shah Alam City Council) By-Laws 2005. This research further seeks guidance by comparing the available laws in Malaysia with the United Kingdom and Australia. The importance of having proper laws in governing the issues relating to children's safety in Malaysia is to safeguard the rights of the aggrieved party when injuries happened to children while playing in playground. This study is confined to the situation in Shah Alam and reference made to the rules and regulations therewith shows the need to have a more comprehensive legal approach in the development of children's playground.